Optimization of cutting conditions on tool life in face milling spheroidal graphite cast iron using Taguchi method - Bahurdin, Mohamad Maaroff (2012)
The aim of this study was to determine the optimum cutting condition for face milling when machining the nodular cast iron. The cutting conditions consist of the cutting speed, the feed per tooth and the depth of cut. The original problem arose in the crankshaft machining-line of the Proton engine shop where the face milling cutting tool frequently changed due to premature of tool life. As a result, the productivity of this production line was decreased. This problem occurred due to the enhancement of the raw-cast hardness, and no detail study was made on the cutting condition by the engine shop. This study was carried in three experiments; the preliminary experiment,optimization experiment and confirmation experiment. All experiments used the same tool and the same material of the engine shop.The preliminary experiment aimed to determine and benchmark the performance of the cutting tool and surface roughness when machined in the laboratory environment. Taguchi optimization method was applied for optimization experiment. This experiment aims to regulate the machining parameters of three parameters at three levels. A L9 orthogonal array,signal-to-noise ratio and analysis of variance (ANOVA) were applied in order to determine and analyzed the optimal cutting condition. The confirmation experiment was conducted using the suggested cutting condition obtained from the optimization experiment in order to validate the result. The result of the preliminary experiment showed that the volume of material removes using the current practice cutting condition was about two hundred and fifty cubic centimetres. The average surface roughness measured was about point six micrometers. The optimization result showed that the optimum cutting condition capable to remove the material more than four hundred cubic centimetres with the surface roughness measured about point six micrometers. Comparison between both experiments shows that the result was different for about forty percent. This indicated that the optimization experiment was successfully determined the optimal cutting condition. Results obtained by Taguchi method match closely with ANOVA and cutting speed is most influencing parameter. The confirmation experiment conducted also agreed on the optimization experiment result where the result of material removes volume and surface roughness was the same. The results show that there is a proper way to determine the optimal cutting conditions other than trial-and-error method, which indirectly saves operating costs. It is recommended to the engine shop to adjust its current cutting conditions according to the findings of this study. Research on the same topic by using another grade inserts are recommended for further study.